G‘AFUR G‘ULOM AND FOLKORAL CREATIVITY - Atajanov Sarvar Samandarovich (Journals Park Publishing, 2024)
This article analyzes the poet's important information about boasters and jokers, as well as his mastery in using proverbs, various phraseological expressions, praises, and curses in his poetry.
Keywords: folklore, boast, joke, proverb, phraseological expressions, praise, curse.